Characterising the structure of cognitive heterogeneity in schizophrenia spectrum disorders. A systematic review and narrative synthesis. (December 2019) - Carruthers, Sean P.; Van Rheenen, Tamsyn E.; Gurvich, Caroline; Sumner, Philip J.; Rossell, Susan L.
Highlights: Three distinct cognitive subgroups exist within SSD. A subgroup characterised by relatively intact cognitive functioning. An intermediate subgroup characterised by moderate/mixed levels of impairment. A globally impaired subgroup characterised by severe cognitive dysfunction. Abstract: The aim of the present review was to systematically summarise our current understanding of the structure of the cognitive heterogeneity that exists within schizophrenia spectrum disorder (SSD). Fifty-two relevant studies were identified from January 1980 to March 2019 that investigated cognitive subgroups within SSD. Twenty-five studies employed classification criteria based on current neuropsychological function, 14 studies employed various data-driven subgrouping methodologies and 13 studies investigated putative cognitive symptom trajectories. Despite considerable methodological variability, three distinct cognitive subgroups reliability emerged; a relatively intact cognitive subgroup characterised by high cognitive performance, an intermediate cognitive subgroup defined by mixed or moderate levels of cognitive function/dysfunction and a globally impaired subgroup characterised by severe cognitive deficits. Whilst preliminary evidence suggests that these subgroups may have further investigative relevance in and of themselves, additional research is required and discussed. A set of reporting guidelines are also presented to overcome the methodological inconsistencies identified in the reviewed literature.